Przechadzka z „Innym” - Białek, Ireneusz (Życie z niepełnosprawnością w świecie VUCA, 2022)
Ireneusz Białek’s essay A Stroll with an “Other” is an attempt at looking at the mysterious world of persons with disabilities, if such a world truly exists in the first place. It is a reflection on ‘Another Disabled Person’ including references to the oeuvre of Ryszard Kapuściński and the author’s own experience of disability as well successes and failures determined by it. It is on their base that he formulates several questions he finds important, posed to himself but also others, and ‘Other Persons with Disabilities’ in particular. This text is a labyrinth in which the reader needs to find him/ herself on their own, pointing to some nooks and crannies where answers to the questions posed may appear. Last but not least, it is an invitation to a walk together along one of Cracow’s charming alleys.